POLA KUMAN PADA PASIEN BARU INFEKSI MENULAR SEKSUAL DI POLIKLINIK KULIT DAN KELAMIN RSUP. PROF. Dr. R.D. KANDOU MANADO PERIODE NOVEMBER 2010 S.D NOVEMBER 2012 - Tanaiyo, Fitri Yanti; Soeliongan, Standy; Porotu’o, John (e-Biomedik, 2014)
Abstract: STIs (Sexually Transmitted Infections) are diseases which is transmitted through sexual contact (oral, vaginal, anal) with an infected person. WHO (World Health Organization) in 2001 estimated STI patients around the world as much as 340 million people. This research uses descriptive retrospective study in November 2012 to January 2013 where conducted in the department of dermatology clinic at Prof.Dr.R.D.Kandou General Hospital, Manado. The research sample is a new STI patients who come for treatment at the clinic that had microbiological laboratory examination such as direct examination and gram staining examination. Based on data collected from 163 patients who had a new IMS and had direct microbiological examination for trichomonas only one patient was found positive result that 38 years old female. Based on gram stain examination, 83 patients were found positive results. Based on gram stain examination for pseudohyphae, 24 (14,7%) patients with positive results. 18 of them females and 11 where in the age group 20-29 years. Among 163 patients there were 10 (6,1%) patients were positive results of gram positive bacilli, seven among them are females and in all age groups. For gram negative bacilli obtained positive results in 24 (14,7%) of 163 patients, 15 of them are females and most in the age group 20-29 years. Among 163 patients, 9 patients (5,5%) were found positive results for gram positive diplococcus, 8 males and the highest number in the age group 20-29 years for gram negative diplococcus obtained positive results in 16 (9,8%) of 163 patients, 15 of them in males and highest number in the age group 20-29 years. The presence of STIs are in increasing every year due to lack of attention from the healthy centers and the lack of knowledge about the causes and consequences of STIs. The socialization of STIs and adolescence's sex education are important for STIs preventions. Keywords: Sexually Transmitted Infection, Sexually Transmitted Disease Abstrak: IMS (Infeksi Menular Seksual) adalah penyakit yang menular melalui hubungan seksual (oral, vaginal, anal) dengan orang yang telah terinfeksi. WHO (World Health Organization) pada tahun 2001 memperkirakan penderita IMS diseluruh dunia sebanyak 340 juta orang. Jenis penelitian ini menggunakan metode deskriptif retrospektif dengan waktu penelitian pada bulan November 2012 sampai Januari 2013 yang dilaksanakan di Poliklinik Kulit dan Kelamin RSUP Prof.Dr.R.D.Kandou, Manado. Sampel penelitian adalah pasien IMS baru yang datang berobat yang telah menjalani pemeriksaan laboratorium mikrobiologi langsung dan pewarnaan gram. Berdasarkan data yang diambil dari 163 pasien yang telah dilakukan pemeriksaan mikrobiologi langsung untuk trikomonas didapati satu pasien yang hasilnya positifyaitu pasien perempuan usia 38 tahun. Dari pewarnaan gram didapatkan 83 pasien dengan hasil positif. Untuk pseudohifa, hasil positif pada 24 orang (14,7%), 18 diantaranya pada perempuan dan 11 diantaranya pada kelompok usia 20-29 tahun. Dari pewarnaan gram didapati dari 163 pasien ada 10 orang (6,1%) yang hasil positif basil gram positif, 7 diantaranya pada perempuan dan terdapat pada semua kelompok usia. Untuk basil gram negatifdidapatkan hasil positif pada 24 (14,7%) dari 163 pasien, 15 diantaranya pada perempuan dan terbanyak pada kelompok usia 20-29 tahun. Dari 163 pasien didapatkan hasil positif untuk diplokokus gram positif sebanyak 9 orang (5,5%), 8 diantaranya pada pria danjumlah terbanyak pada kelompok usia 20-29 tahun. Untuk diplokokus gram negatif didapatkan hasil positif pada 16 (9,8%) dari 163 orang pasien, 15 diantaranya pada pria dan terbanyak pada kelompok usia 20-29 tahun. Terjadinya kasus IMS yang meningkat setiap tahunnya diduga karena kurangnya perhatian dari pusat kesehatan dan kurangnya pengetahuna tentang sebab dan akibat dari IMS. Banyaknya sosialisasi tentang IMS dan pendidikan seks pada usia dini pent ing untuk pencegahan IMS. Kata kunci: Infeksi Menular Seksual, Penyakit Menular Seksual